Identification Of Vegetable Fat Formulations on Hardness, Cleaning and Conditioning of Solid Soap - Hulyadi, Hulyadi; Muhali, Muhali; Prayogi, Saiful; Azmi, Irham; Firdaus, Laras; Suryati, Suryati; Mirawati, Baiq; Gargazi, Gargazi (Journal of Authentic Research, 2025)
This study aims to examine the effect of varying vegetable oil compositions (coconut, palm, and olive) on the physical and chemical qualities of solid soap, specifically in terms of hardness, cleansing ability, and moisture content. This study used a laboratory experiment with five soap formulas combining various vegetable oil compositions. The results showed that the formula with a combination of 60% coconut oil and 40% palm oil produced the soap with the highest hardness, while the formula with a combination of 60% coconut oil and 40% olive oil provided the best moisture content. The soap with a composition of 60% coconut oil and 40% palm oil also demonstrated better cleaning ability, thanks to the lauric acid content in coconut oil, which has antibacterial properties. This study recommends the use of a combination of coconut and palm oils to produce soap with the best quality in terms of hardness and cleansing ability, and coconut and olive oils for soap with greater skin moisturizing properties. It is hoped that this research will contribute to the development of the natural soap industry in Indonesia, reduce dependence on imported raw materials, and increase the competitiveness of natural soap products in the global market.